Body Language: 'Spellbinding storytelling' Val McDermid - Turner, A. K. (Bonnier Zaffre, 2021)
THE DEAD CAN TALK - WE JUST NEED TO LISTEN . . . Camden mortuary assistant Cassie Raven has pretty much seen it all. But this is the first time she's come face to face with someone she knew on the slab. Someone she cared about. Geraldine Edwards, the teacher responsible for her returning to education after she got ensnared in a life of drugs. The woman who acted as a second mother to the orphaned Cassie. Deeply intuitive and convinced that she can pick up the last thoughts of the dead, Cassie senses that there must be more to the ruling of an accidental death. With Mrs E.'s evasive son demanding the release of his mother's body, Cassie knows that time is running out to find answers. Is her grief making her see things that aren't there? Or is her intuition right, and there's something more sinister to Mrs E's death than the ME thinks? Harbouring an innate distrust of the police, Cassie sets out to investigate the death and deliver justice for the woman who saved her life. For fans of Elly Griffiths' Ruth Galloway series and Kathy Reichs' Temperance Brennan comes a new heroine for forensic medicine.